Sensitivity of normal and malignant human lymphocytes to 5-aminolevulinic acid-mediated photodynamic damage - Gamaleia, N.F.; Shishko, E.D.; Gluzman, D.F.; Sklyarenko, L.M. (Experimental Oncology, 2008)
Aim: To compare the sensitivity of normal and malignant human lymphocytes to 5-aminolevulinic acid (ALA) — mediated photodynamic damage. Methods: Blood lymphocytes isolated by Ficoll-sodium metrizoate density gradient from healthy donors (6) and hematologic patients (20) with different forms of lympholeukemia, and also transformed lymphocytes of human B-cell (Raji, Namalwa) and T-cell (MT-4, HUT-78) lines were inestigated. Diagnoses of chronic lymphoproliferative disorders were made on the grounds of morphological, cytochemical and immunocytochemical studies of peripheral blood and bone marrow cells, with immunophenotype determination by monoclonal antibodies to differentiation antigens of T, B lymphocytes and NK cells and immunocytochemical ABC-AP method. Cells of leukemic B- and T-cell lines were cultured in standard RPMI-1640 medium. For photodynamic treatment, the cells were incubated with ALA and then irradiated by a helium-neon laser (wavelength of 633 nm). The number of dead cells was determined in 20 h with trypan blue dye exclusion test. Results: The striking difference in responsiveness to ALA-mediated photodynamic treatment (ALA-PDT) between normal lymphocytes and cells isolated from lymphatic leukemia patients was established. A bulk of leukemic cells (mean for 10 patients with B-CLL — 62.06 ± 4.03%) were destroyed under the lowest ALA-PDT doses tested: 1 mM ALA, irradiation dose of 25 J/cm2. However, it was virtually impossible to attain any appreciable damage of lymphocytes from healthy donors even with the highest treatment doses (5 mM ALA, 150 J/cm2). High sensitivity to ALA-PDT of malignant lymphocytes was confirmed in experiments with human T- and B-cell leukemic cell lines, and in these experiments, an anomalous reaction to the treatment of Raji cells was also detected. The mechanisms of the difference between normal and malignant lymphocytes are discussed in terms of altered heme-synthesis processes in malignant cells. Conclusions: 1) It is shown for the first time that blood lymphocytes from lymphatic leukemia patients are highly sensitive to the damage with ALA-PDT while lymphocytes of normal donors are practically not damaged. 2) Transformed lymphocytes of human T-cell lines are more sensitive than lymphocytes of B-cell lines. 3) Lymphocytes of the Raji line display anomalous dose-effect dependence with ALA-PDT. 4) It is proposed to evaluate the drastic difference in ALA-PDT responsiveness of normal and malignant lymphocytes as a possible simple and low-traumatic test for B-CLL screening among the elderly people. Цель: изучить чувствительность к фотодинамическому воздействию, опосредованному 5-аминолевулиновой кислотой (АЛК),
нормальных и малигнизированных лимфоцитов человека. Методы: объектом исследования служили лимфоциты, выделенные
с помощью градиента плотности фиколл-верографина из крови здоровых доноров (6) и гематологических больных (20)
с различными формами лимфолейкозов, а также трансформированные лимфоциты В-клеточных (Raji, Namalwa) и Т-клеточных
(МТ-4, HUT-78) линий человека. Диагноз хронического лимфопролиферативного заболевания ставили на основании
морфологического, цитохимического и иммуноцитохимического исследования периферической крови и клеток костного мозга;
иммунофенотипирование проводили с использованием панели моноклональных антител к дифференцировочным антигенам
Т-, В-лимфоцитов, NK-клеток и АВС-АР-метода. Трансформированные лимфоциты клеточных линий культивировали в
стандартной RPMI-1640 среде с 10% эмбриональной телячьей сывороткой. Для фотодинамического воздействия клетки
инкубировали с 1,0–5,0 мМ АЛК в течение 4 ч и облучали гелий-неоновым лазером (длина волны – 633 нм), варьируя дозу от
10 до 150 Дж/см2
. Количество погибших клеток после дополнительной 20-часовой инкубации определяли с помощью теста
с трипановым синим. Результаты: показано, что нормальные и малигнизированные лимфоциты человека резко отличаются по
чувствительности к АЛК-опосредованному фотодинамическому действию (АЛК-ФД). Значительная часть лимфоцитов крови
больных лейкозом (в среднем 62,06 ± 4,03% у 10 пациентов с В-клеточным хроническим лимфолейкозом, В-ХЛЛ) погибала
при минимальных параметрах воздействия (1 мМ АЛК, доза облучения 25 Дж/см2
), тогда как даже наивысшая доза (5 мМ
АЛК, 150 Дж/см2
) не влияла на жизнеспособность нормальных лимфоцитов. В опытах in vitro в Т-клеточных линиях отмечали
больший процент гибели клеток, чем в В-клеточных. При этом линия Raji отличается парадоксальным отсутствием зависимости
количества погибших клеток от дозы воздействия, что, по-видимому, связано с известным для этой линии дефектом сигнальных
путей апоптоза. Обсуждаются вероятные механизмы установленных отличий между нормальными и малигнизированными
лимфоцитами в контексте альтерации процессов синтеза клетками гема при малигнизации. Выводы: 1) впервые показано,
что малигнизированные лимфоциты крови больных лимфолейкозом проявляют высокую чувствительность к АЛК-ФД
при фактическом отсутствии такой чувствительности у лимфоцитов здоровых доноров; 2) озлокачествленные лимфоциты
Т-клеточных линий более чувствительны к АЛК-ФД по сравнению с В-клеточными; 3) для клеток линии Raji установлена
аномальная зависимость доза/эффект; 4) на основе полученных результатов предложен простой и малотравматичный тест
для скрининга пожилых людей на наличие В-ХЛЛ.